Guardians of the Lifeworld: Phenomenological Dwelling and Resistance in an Age of Acceleration - Healey-Benson, Felicity; Johnson, Mike (Proceedings of the International Conference on Networked Learning, 2026)
This paper draws inspiration from phenomenology and Marvel Entertainment’s Guardians of the Galaxy (GotG) to elevate and guard the practices of scholarship, as one response to the encroachment and infiltration of large language models (LLMs) and generative artificial intelligence (GenAI) into academic knowledge work, thinking in particular. LLMs and GenAI may offer to accelerate labourious knowledge work, and gild with kudos those who thus leverage it, for example in compiling entire literature reviews on demand. We contend that automating aspects of scholarship impoverishes the necessarily relational, embodied and ethical activity of scholars. In this AI-infiltrated era, we present a novel (and fun!) phenomenological stimulant for delegates to the networked learning conference. Rather than the just the usual canonical philosophical writers, our inspiration draws upon some of the main characters of GotG. We argue that GotG may be encountered, attending to their narrative arcs: their dialogue, gesture, sacrifice and relation. These facets, as they play out in moments of grief and generosity, etc. can help us to reflect on our own attempts at scholarly practice through current GenAI-troubled tensions. These lived tensions, as they may texture networked collaborative academic work, are briefly elaborated through four fragments: the disappeared voice, the stillness that registers as absence, the question that got automated and, the speed that erases process. These fragments share a flavour of what the Guardians may address. Brief depictions and insights from the Guardians we include are informed by repeat viewing of the GotG movie trilogy and fan wikis. We begin with Star-Lord, a figure of fragmentation and longing, of disconnection and yet drawing repeatedly back from the brink through music and the call of what matters. We introduce Gamora, as guarding the possibility of ethics amid torrid interminable violence. For us, Rocket and Nebula guard the possibility of healing without erasure. Groot and Mantis guard the quiet forms of knowing. Drax guards the fragility of interpretation. We invite delegates to join us in drawing playful resilience and hope from our GotG interpretive companions and celebrate the freedom to deliberate unplugged inception into scholarly discourse, to guard the conditions of thought and thinking itself.